2017
DOI: 10.1039/c7ta01285c
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the potentials, solubilities and stabilities of metal-acetylacetonates for non-aqueous redox flow batteries using density functional theory calculations

Abstract: New active materials are needed to improve the performance and reduce the cost of non-aqueous redox flow batteries (RFBs) for grid-scale energy storage applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 51 publications
2
51
0
1
Order By: Relevance
“…The D values reported in acetonitrile ranged from 0.56 © 10 ¹5 to 1.5 © 10 ¹5 cm 2 s ¹1 , depending on the electrochemical techniques. 14,15,22,26 The D value of Fe(acac) 3 in BMPTFSA was much smaller than those in acetonitrile, reflecting the higher viscosity (73 mPa s) of BMPTFSA containing 10 mM Fe(acac) 3 . As abovementioned, the negative redox potentials of [Fe(CN) 6 ] 3¹ and Fe(acac) 3 are considered suitable for the anolyte of the redox flow batteries.…”
Section: ¹1mentioning
confidence: 99%
See 1 more Smart Citation
“…The D values reported in acetonitrile ranged from 0.56 © 10 ¹5 to 1.5 © 10 ¹5 cm 2 s ¹1 , depending on the electrochemical techniques. 14,15,22,26 The D value of Fe(acac) 3 in BMPTFSA was much smaller than those in acetonitrile, reflecting the higher viscosity (73 mPa s) of BMPTFSA containing 10 mM Fe(acac) 3 . As abovementioned, the negative redox potentials of [Fe(CN) 6 ] 3¹ and Fe(acac) 3 are considered suitable for the anolyte of the redox flow batteries.…”
Section: ¹1mentioning
confidence: 99%
“…In the electrochemical field, the redox reaction using tris(acetylacetonato)iron complex (Fe(acac) 3 ) has been examined in organic electrolytes and deep eutectic solvents for such applications as redox flow batteries and photoelectrochemical cells. [14][15][16] We have reported that the metal complexes with acac ¹ , such as Pd(acac) 2 and Pt(acac) 2 , are stable in TFSA ¹ -based ionic liquids. [17][18][19] In the present study, the redox properties of Fe(acac) 3 were investigated in BMPTFSA.…”
Section: Introductionmentioning
confidence: 99%
“…High-throughput computational screening offers the possibility of exploring thousands of molecules for desirable properties without the need for experimental trial and error. [23][24][25] The computational results can provide key insights into structureactivity properties that may be used in the design and tuning of new molecules for electrochemical energy storage. The majority of theoretical studies have been conducted on the quinone family (benzoquinone, naphthoquinone, and anthraquinone) whose redox potential and solvation free energies strongly depend on the chemical nature of electron donating groups (EDGs) and electron withdrawing groups (EWGs) attached to the basic quinoyl skeleton.…”
Section: Introductionmentioning
confidence: 99%
“…Milestone examples of non-aqueous metal-based RFBs include Ru- [32], Fe- [32], U- [33], V- [34,35], Mn- [36], Cr- [37], Ni- [38], Co- [39], and W [40]-containing systems. It is worthy to note that efforts to develop more efficient electrolytes for non-aqueous RFBs have mostly been empirical, from both theoretical and experimental perspectives, with limited attempts toward the rational design of structural, electronic, and other RFB-relevant properties [41][42][43][44]. It is clear that there is an urgent need to develop more affordable and efficient RFBs to meet the world's growing energy storage demands.…”
Section: Introductionmentioning
confidence: 99%